Why people violate the law? a review of literature on legal socialization - Jamaludin, Nurul Nadia; Hasbullah, Muslihah (Asian Scholars Network, 2020)
Although Malaysia is increasingly enforcing specific laws and regulations on various civil and criminal matters, there are still a number of people who refuse to comply with the laws. As an example, recently government of Malaysia has enforced law that banning smoking behavior in restaurant areas. Unfortunately a number of smokers ignored the law and they do not even care with the warning and penalties announced by the authority. This is an example of non-compliance behaviour. What makes people dare to violate the law? This question requires specific explanation about the differences in the developmental processes of adult attitudes towards the law which is directly tied to individuals’ compliance with the law and cooperation with the legal authorities. Based on the previous studies, the compliance and non-compliance behaviours are as a result of the development of legal socialization processes. Therefore the main aim of this article is to analyse the factors or driving forces that influence the development of legal socialization in an individual. The method used in this study was through reviewing the research findings available in the academic databases. This paper concludes that positive driving forces will develop positive legal socialization which finally has a greater chance to produce compliance behaviour.